Carving a service quality niche for Sukuk: a case study of National Bonds in the UAE. (2018) - Baydoun, Nabil; Anwar, Syed Aziz
Sukuk products have come to position themselves prominently on the landscape of capital markets. Available evidence indicates that primary Sukuk issuances reached $100 billion in 2017 compared with $88.28 billion in 2016. This figure is likely to reach $200 billion in 2018 (Thomson and Reuters, 2016; S&P Global, 2018). It is also remarkable that Sukuk market has been patronised by both Muslim and non-Muslim investors. In view of the great potential of Sukuk, National Bonds Corporation PJSC (National Bonds), a private joint stock shareholding company in the UAE, has created the National Bonds Sukuk Trading Platform to meet the needs of its customers. Our paper tests the effectiveness of the platform in terms of service quality through an empirical exercise in the UAE. The paper, we hope, would have interesting implications for decision making.